This preview shows pages 1–13. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Chapter 4 Pure Bending Ch 2 Axial Loading Ch 3 Torsion Ch 4 Bending  for the designing of beams and girders 4.1 Introduction A. Eccentric Loading B. Pure Bending 4.2 Symmetric Member in Pure Bending M = Bending Moment Sign Conventions for M:  concave upward  concave downward Force Analysis Equations of Equilibrium x dA = x z dA = ( ) x y dA M  = F x = 0 M yaxis = 0 M zaxis = 0 xz = xy = (4.1) (4.2) (4.3) 4.3 Deformation in a Symmetric Member in Pure Bending Assumptions of Beam Theory: 1. Any cross section to the beam axis remains plane 2. The plane of the section passes through the center of curvature (Point C). Plane CAB is the Plane of Symmetry The Assumptions Result in the Following Facts: 1. xy = xz = 0 xy = xz = 0 2. y = z = yz = 0 The only nonzero stress: x 0 Uniaxial Stress The Neutral Axis (surface) : x = 0 & x = 0 L = ' ( ) L y = ' = L L Where = radius of curvature = the central angle Line JK (4.5) Before deformation: DE = JK Therefore, Line DE (4.4) (4.6) ( ) y y = =  The Longitudinal Strain x = l l o  = = =  x x y L y x varies linearly with the distance y from the neutral surface (4.9) The max value of x occurs at the top or the bottom fiber: = m c (4.8) Combining Eqs (4.8) & (4.9) yields x m y c =  (4.10) 4.4 Stresses and Deformation is in the Elastic Range For elastic response Hookes Law x x E = ( ) x m y E E c =  x m y c =  max x m y y c c =  =  Therefore, (4.11) (4.10) (4.12) Based on Eq. (4.1) x dA = max x m y y c c =  =  ( ) m x m y dA dA ydA c c = =  = (4.1) (4.12) (4.13) Hence, ydA first moment of area = = Therefore,...
View
Full
Document
 Fall '11
 Wu

Click to edit the document details